Malnutrition Treatment Centre in District Baran, Rajasthan Appraisal of Performance - Gupta, Pankaj Kumar; Mulla, Shakila; Baig, Vaseem Naheed (Indian Journal of Community Health, 2015)
Background: Rajasthan has topped the list of states with kids being born underweight as per Annual Health Survey (1). Malnutrition treatment centres (MNTC) have been started in District Baran, from 2006(2). Having started functioning for so many years, it is essential to evaluate its function so as to come forward with recommendations for future improvement. Aims & Objectives: Current study was conducted with an objective to analyze the impact of interventional measures in improving the health and nutritional status of severe malnourished children admitted at one of the MNTC in district Baran. Material and Method: Observational Prospective study was conducted at Community Health Centre (CHC) Atru MNTC, District Baran, Rajasthan. Children admitted were observed for weight gain during their stay at MNTC and rate of follow-up was also observed. Result: A statistically significant difference was obtained between the weight of children who stayed for 1-6 days and children who stayed for 7-28 days in MNTC. 54.1% children cured after treatment. Follow-up rate was very poor 51.5%, 30.3%, 23.2%, and 18.2% over the four follow-up visits. Conclusion: The MNTCs were effective in improving and saving the life of admitted children, but the effects were not sustained due to inadequate stay and poor follow up rate